(untitled) (Journal of the College of Basic Education, 2022)
Recently, the game of five-a-side football for boys and girls has entered the field of local and international competitions, and its practices have become widespread in societies.As a result of the increasing pressures of sports competitions, to which athletes may respond physically and mentally in a way that may affect their performance, which makes them lose focus on performance.Suger Man (1998) indicated: What athletes are trying to accomplish and what experts and psychologists are seeking to help athletes and sports teams achieve and achieve, calls for increased interest and study of some of the characteristics of the best performance. The player can perform his best performance in tournaments when he feels that he has reached a certain mental and psychological point (10: 31).